2011
DOI: 10.1002/mrm.23165
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of blood‐brain barrier permeability in human using dynamic contrast‐enhanced MRI with fast T1 mapping

Abstract: Breakdown of the blood-brain barrier (BBB), occurring in many neurological diseases, has been difficult to measure noninvasively in humans. Dynamic contrast-enhanced magnetic resonance imaging measures BBB permeability. However, important technical challenges remain and normative data from healthy humans is lacking. We report the implementation of a method for measuring BBB permeability, originally developed in animals, to estimate BBB permeability in both healthy subjects and patients with white matter pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 23 publications
5
58
1
Order By: Relevance
“…The leakage rates observed in this study were in accordance with values found in a previous study in patients with white matter pathology (∼2.0·10 −3 min −1 ) and a study in patients with mild cognitive impairment (∼1.0·10 −3 min −1 ), despite differences in image acquisition and analysis methods. The fairly low CVs and moderate to excellent ICCs observed in this study indicate that the reproducibility of measuring subtle leakage is moderate to excellent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The leakage rates observed in this study were in accordance with values found in a previous study in patients with white matter pathology (∼2.0·10 −3 min −1 ) and a study in patients with mild cognitive impairment (∼1.0·10 −3 min −1 ), despite differences in image acquisition and analysis methods. The fairly low CVs and moderate to excellent ICCs observed in this study indicate that the reproducibility of measuring subtle leakage is moderate to excellent.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, DCE‐MRI is increasingly applied to estimate subtle leakage of the BBB in cerebrovascular and neurodegenerative diseases (e.g. cerebral small vessel disease [cSVD] and Alzheimer's disease) . These studies have found increased leakage of the BBB, which confirmed the role of the breakdown of this barrier in the pathophysiology.…”
mentioning
confidence: 91%
“…Studies performed in mice have demonstrated that observations of leakage with MRI using gadolinium reflect leakage patterns observed after injection with exogenous tracers (Nitta et al 2003;Navarathna et al 2013;Li et al 2014). DCE-MRI has been used to show that BBB leakage is a characteristic of several neurodegenerative diseases in humans, including multiple sclerosis (Taheri et al 2010;Gaitán et al 2011;Ingrisch et al 2012;Cramer et al 2015;Montagne et al 2015) and Alzheimer's disease (Montagne et al 2015;van de Haar et al 2016a, b).…”
Section: Defining Bbb Permeabilitymentioning
confidence: 99%
“…To test this hypothesis, we used MR contrast agent (MRCA)‐assisted MRI as used extensively in assessing BBB injury after stroke both clinically and experimentally . MRCA‐MRI has the advantage of achieving relatively high resolution and being relatively noninvasive, allowing a subject to be monitored over time.…”
Section: Introductionmentioning
confidence: 99%